1 Logarithm Calculator | log(x) Calculator
1

Logarithm Calculator

Calculate logarithm of a number to any base:

log  
Result:
Description:

* Use e for scientific notation. E.g: 5e3, 4e-8, 1.45e12

When:

b y = x

Then the base b logarithm of a number x:

logb x = y

Anti-logarithm calculator

In order to calculate log-1(y) on the calculator, enter the base b (10 is the default value, enter e for e constant), enter the logarithm value y and press the = or calculate button:

 
Result:

When

y = logb x

The anti logarithm (or inverse logarithm) is calculated by raising the base b to the logarithm y:

x = logb-1(y) = b y

Logarithm rules

Logarithm product rule

logb(x × y) = logb(x) + logb(y)

Logarithm quotient rule

logb(x / y) = logb(x) - logb(y)

Logarithm power rule

logb(x y) = y × logb(x)

Logarithm base switch rule

logb(c) = 1 / logc(b)

Logarithm base change rule

logb(x) = logc(x) / logc(b)

 

 


See also
1
Home

Do my Math Homework 1
MATH CALCULATORS
The condition with one obscure, which after the opening of sections and throwing of comparable individuals takes the structure ah + b = 0, where an and b are discretionary numbers, is known as a direct condition with one obscure. Today we will see how to explain these straight conditions. - For instance, all conditions: 2x + 3 = 7 - 0.5x; 0.3x = 0; x/2 + 3 = 1/2 (x - 2) - straight. The estimation of the obscure that turns around the condition to the right balance is known as the arrangement or the foundation of the condition. For instance, in the event that we substitute the number 2 in the condition 3x + 7 = 13 rather than the obscure x, at that point we get the genuine correspondence 3 · 2 +7 = 13. Henceforth, the worth x = 2 is the arrangement or the base of the condition. Furthermore, the worth x = 3 does not change over the condition 3x + 7 = 13 to a genuine balance, since 3 · 2 +7 ≠ 13. Subsequently, the worth x = 3 isn't an answer or a foundation of the condition. The arrangement of any straight conditions is diminished to the arrangement of conditions of the structure ah + b = 0. Move the free term from the left half of the condition to one side, changing the sign before b to the inverse, we get ah = - b. On the off chance that a ≠ 0, at that point x = - b/a.

Users write Now: CEHATOP PRO • a year ago You have heard about the order of actions!?!?

More Calculators: limit calculator 1
1